Zbrodnie na mieszkańcach terenów okupowanych. Podstawy karania w świetle wyroków amerykańskich i brytyjskich trybunałów wojskowych 1945–1947 - Basak, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
The subject of this paper is a judiciary construction of Article 46 of the Regulations Respecting the Laws and Customs of War on Land annex to 1907 Hague Convention which orders occupant to respect lives, honour and family rights of inhabitants of occupied territory. American and British tribunals gained territorial and rem jurisdiction of the courts of “liberated countries” as stated by Moscow Declaration. Without sharing their experiences, they ruled in cases which had no connection to military operations, the perpetrators of which were mostly civilian and the victims of which were outside occupied territories and usually were not citizens of adjudicating empires. Finally, in case of American tribunals, some of the punished actions were committed during the time when the United States remained neutral. The established conclusions show that crimes against inhabitants of occupied territories can also be committed by civilian citizens of occupant and on his own territory. The fact that they happen as a result of criminal deportations does not absolve occupant of responsibility because he still remains under an obligation to enforce Article 46 with respect to deportees’. This obligation also extends to children born after deportation. Any attempts to circumvent Article 46 by illegal annexation of occupied territories is ineffective and does not shield perpetrators from criminal responsibility for violating the above-mentioned rights. Execution can be secured by any state in hands of which criminals find themselves. Neither the fact that victims are citizens of allied states nor the fact that adjudicating state was not participating in hostilities at the time of crime’s commission, creates any obstacle in this context. These conclusions apply to the relatively narrow part of postwar criminal procedure concerning war crimes. They indicate that, while constructing Article 46, the examined tribunals gave this rule an objective and subjective scope which was not provided by the authors of Regulations. By widening the grounds for penalization for violating this rule, they ipso facto widened the scope of protection guaranteed by it. Although this construction may appear obvious from today’s perspective, it nevertheless was a result of fi erce disputes between process sides. The contemporary obviousness of this interpretation is also an evidence of the importance of legal precedents established during that time. It particularly pertains to the rule of universality in the punishing of war crimes.
Keywords: zbrodnie wojenne; tereny okupowane; karanie; amerekańskie trybunały wojskowe; brytyjskie trybunały wojskowe